Electroacupuncture reduces injury to the blood-brain barrier following cerebral ischemia/ reperfusion injury☆ - Peng, Yongjun (Medknow Publications & Media Pvt Ltd, 2012)
This study used electroacupuncture at Renzhong (DU26) and Baihui (DU20) in a rat model of cerebral ischemia/reperfusion injury. Neurological deficit scores, western blotting, and reverse transcription-PCR results demonstrated that electroacupuncture markedly reduced neurological deficits, decreased corpus striatum aquaporin-4 protein and mRNA expression, and relieved damage to the blood-brain barrier in a rat model of cerebral ischemia/reperfusion injury. These results suggest that electroacupuncture most likely protects the blood-brain barrier by regulating aquaporin-4 expression following cerebral ischemia/reperfusion injury.